2
$\begingroup$

Padoa's inequality is named after Alessandro Padoa (1868-1937):

Let $a$, $b$, $c$ be sidelengths of a given triangle $\triangle ABC$ then

$$(b+c-a)(c+a-b)(a+b-c) \le abc .$$

My question: Is the following generalization of Padoa's inequality corect?

Let $a_i>0$ for $1\le i\le n$ and let $$S:=a_1+a_2+....+a_n.$$ Suppose that $$b_i:=S-(n-1)a_i \ge 0\quad\text{ for} \quad 1\le i\le n.$$ Then

$$\prod_{i=1}^n b_i \leq \prod_{1}^{n} a_i .$$

$\endgroup$
5
$\begingroup$

Since $a_i=\frac{S-b_i}{n-1}=\frac{\sum_j b_j -b_i}{n-1}$ we can write $$\prod_{i=1}^n a_i=\prod_{i=1}^n \left(\frac{\sum_{j\neq i}b_i}{n-1}\right)\geq \prod_{i=1}^n \left(\prod_{j\neq i}b_i\right)^{1/n-1}=\prod_{i=1}^n b_i$$ by the Arithmetic-Geometric mean inequality.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.